Rede de interações aves-artrópodes: Padrões de alimentação na mata atlântica brasileira - Iuksz, Mariana Malosti (Universidade Federal de São Carlos, 2023)
Interaction networks are used to provide a better understanding of ecological communities and their structures. In this study, we analyzed bird-arthropod interactions in the Brazilian Atlantic Forest. The survey of studies was carried out in the Web of Science and Google Scholar platforms using the following keywords in combination: “birds”, “Atlantic Forest” and “diet”. Our hypotheses are: (1) birds will consume a small amount of prey in relation to the total number found in the net, with less than half of possible connections (links) with arthropods, presenting a low value for the specialization index for the network (H2’); (2) The core of network generalists must include less than 50% of bird species detected to consume arthropods; (3) The network will have a modular structure. All analyzes were carried out using R software in version 4.3.2. We found 16 articles/theses published from 2001 to 2020. The predator-prey interaction network includes 185 bird species and 37 arthropod groups. The network had a total of 1,011 connections (C = 0.148). Total nesting was N =60,163. The modularity was Q = 0.2328. The results corroborate the hypothesis that the network's specialization would be low (H1). The group of generalists included only 33 bird species (17.84%) and 6 arthropod taxa (16.22%) (H2). However, the interaction network did not present a modular structure, as expected for prey-predator networks (H3). The network of interactions allows a new visualization of the relationship between bird species preying on groups of arthropods in the Atlantic Forest, presenting a community with high niche overlap and unstable due to the absence of the modular pattern.
Bird-arthropod interaction: Feeding patterns in the Brazilian Atlantic forest
Keywords: Consumo de Artrópodes; Dieta de Aves; Floresta Neotropical; Interações Predador-presa; Arthropod Consumption; Birds’ Diet; Neotropical Forest; Network Structure; Predator-prey Interactions; CIENCIAS BIOLOGICAS::ECOLOGIA